An Ordinance to Prevent the Use of Fire Arms, § 2, in Charter of the City of Hudson 109 (1868) - (:unkn) unknown (My University, 1855)
No person shall within this city fire or discharge any gun, pistol, cannon or fowling-piece or other fire-arms, unless in defence of his or her property or person, nor let off any squibs, crackers or other fireworks, unless by permission of the city authorities.
Keywords: DISCHARGE